An Augmented Reality-Based Approach for Surgical Telementoring in Austere Environments. (1st March 2017) - Andersen, Dan; Popescu, Voicu; Cabrera, Maria Eugenia; Shanghavi, Aditya; Mullis, Brian; Marley, Sherri; Gomez, Gerardo; Wachs, Juan P.
ABSTRACT: Telementoring can improve treatment of combat trauma injuries by connecting remote experienced surgeons with local less-experienced surgeons in an austere environment. Current surgical telementoring systems force the local surgeon to regularly shift focus away from the operating field to receive expert guidance, which can lead to surgery delays or even errors. The System for Telementoring with Augmented Reality (STAR) integrates expert-created annotations directly into the local surgeon's field of view. The local surgeon views the operating field by looking at a tablet display suspended between the patient and the surgeon that captures video of the surgical field. The remote surgeon remotely adds graphical annotations to the video. The annotations are sent back and displayed to the local surgeon while being automatically anchored to the operating field elements they describe. A technical evaluation demonstrates that STAR robustly anchors annotations despite tablet repositioning and occlusions. In a user study, participants used either STAR or a conventional telementoring system to precisely mark locations on a surgical simulator under a remote surgeon's guidance. Participants who used STAR completed the task with fewer focus shifts and with greater accuracy. The STAR reduces the local surgeon's need to shift attention during surgery, allowing him or her to continuously work while looking "through" the tablet screen.